Pre-induction Stroke Volume Variation as a Predictor of Early Post-induction Hypotension in Non-Cardiac Surgery: A Cross-sectional Observational Study - Marthen Luther King Elmas; Putu Agus Surya Panji; I Ketut Wibawa Nada (Jurnal Anestesiologi dan Terapi Intensif, 2026)
Introduction: General anesthesia induction-related hypotension is common and is associated with postoperative organ injury. Dynamic indices derived from echocardiography may help identify patients at risk, although stroke volume variation (SVV) is conventionally more robust under controlled mechanical ventilation than during spontaneous breathing. We investigated whether pre-induction transthoracic echocardiography-derived SVV was associated with arterial pressure 10 min after induction in adult elective non-cardiac surgical patients. Patients and Methods: This single-centre cross-sectional observational study enrolled consecutive adult patients undergoing elective non-cardiac surgery with general anesthesia at a tertiary hospital (August–September 2022). Pre-induction SVV was measured in the supine position using the left ventricular outflow tract method during standardized spontaneous breathing. Anesthesia was induced with propofol 1.5 mg kg−1, fentanyl 2 µg kg−1, and atracurium 0.5 mg kg−1. Non-invasive arterial pressure was recorded for 10 min after induction. The prespecified primary outcomes were systolic blood pressure (SBP) and mean arterial pressure (MAP) at 10 min. Spearman’s rank correlation was used. Results: Sixty-four patients were analysed (mean age 48.4 yr; 57.8% male; 62.5% ASA physical status II). Mean pre-induction SVV was 13.4% (SD 4.3). Mean systolic blood pressure (SBP) decreased from 116.1 (7.9) mmHg pre-induction to 93.3 (6.3) mmHg at 10 min; mean arterial pressure (MAP) from 93.4 (12.3) to 76.8 (6.1) mmHg. Higher pre-induction SVV correlated with lower SBP at 10 min (Spearman r = −0.494; 95% CI −0.660 to −0.282; P < 0.001) and lower MAP at 10 min (r = −0.676; 95% CI −0.790 to −0.516; P < 0.001). Conclusion: Pre-induction transthoracic echocardiography-derived SVV was associated with lower arterial pressure 10 min after induction. Because the study was observational and measurements were obtained during spontaneous breathing, the findings should be interpreted as hypothesis-generating and warrant confirmation in prospective studies.